THE IMPACT OF THE TRANSITION TO PARENTHOOD ON INTIMACY AND ROMANTIC RELATIONSHIPS AMONG SAME‐SEX COUPLES - Ofira, Citrin (E-Journal VFU, 2025)
The transition to parenthood constitutes a significant and complex stage in every couple’s life, and it brings many changes to the couple’s dynamics, intimacy, and romance. For same‐sex couples, the challenges may be even more complex due to social, legal, and cultural factors. This article will examine the effects of the transition to parenthood on the intimate and romantic relationships among same‐sex couples, relying on current research and examples from around the world. The article emphasizes that: the sexual relationships in same‐sex couples after the transition to parenthood experience a decrease in frequency, mainly due to fatigue, identity changes, and parental pressures. The division of roles within the couple (who is the biological parent, who is the primary caregiver) affects desire and intimacy. The article will recommend strategies for preserving intimacy after the transition to parenthood.